Adrenalectomy for huge solid pheochromocytoma: a challenging surgery or piece of cake?. Issue 8 (22nd August 2019) - Labib, Mahmoud; Ismail, Asmaa; Elmansy, Hazem; Shahrour, Walid; Prowse, Owen; Kotb, Ahmed
ABSTRACT: Pheochromocytoma (PCC) is an uncommon adrenal tumor that is occasionally diagnosed during the work up for patients with uncontrolled hypertension. Treatment of PCC is mainly surgical. This case represents the largest PCC reported to date, which was safely removed.